Guessing PINs, One Partial PIN at a Time - Ashley Sheil; David Malone (Entropy, 2022)
Entering digits of a personal identification number (PIN) is a common form of authentication. One variant of this scheme is to request the digits from a random subset of positions, which is sometimes called a partial PIN. In this paper we consider strategies for guessing the PIN when a partial PIN scheme is in use, which allows the quantification of the strength of this mechanism. We suggest several strategies for guessing the PIN under the assumption that the organisation assigns PINs randomly and requests random positions from the PIN at each login. We present analytic and simulation results from the different strategies and explore their performance when guessing different sizes of PIN and requested subset. We find that the most effective strategies have a reasonable chance of recovering a PIN in tens to hundreds of guesses.